Surveying the HPGe Gamma detector absolute efficiency - Tran, Vien Thi; Doan, Tuyen Quang; Tran, Hao Viet Nhan; Doan, Son Thanh; Nguyen, Tinh Trung (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts